Field Reports, Eugene and Eloise Armstrong, Winter 1990-91 - Armstrong, Eloiseet al; Armstrong, Eugeneet al (1990)
Field reports for the Winter of 1990-1991 submitted by Eugene and Eloise Armstrong featuring a Dickcissel sighting at Booneville in Dallas County, IA on December 3, 1990. Epson - sheet feed